2016
DOI: 10.1093/ckj/sfw063
|View full text |Cite
|
Sign up to set email alerts
|

The impact of haemodialysis arteriovenous fistula on haemodynamic parameters of the cardiovascular system

Abstract: BackgroundSatisfactory vascular access flow (Qa) of an arteriovenous fistula (AVF) is necessary for haemodialysis (HD) adequacy. The aim of the present study was to further our understanding of haemodynamic modifications of the cardiovascular system of HD patients associated with an AVF. The main objective was to calculate using real data in what way an AVF influences the load of the left ventricle (LLV).MethodsAll HD patients treated in our dialysis unit and bearing an AVF were enrolled into the present obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 36 publications
(37 reference statements)
2
24
0
2
Order By: Relevance
“…The major finding in this study is association of left ventricle load with AVF flow only in lower arm, but not in upper arm AVFs. Our study results are in agreement with Basile et al (21), showing that higher AVF flow (more commonly seen in upper arm access) failed to associate with higher cardiac risk.…”
Section: Discussionsupporting
confidence: 93%
“…The major finding in this study is association of left ventricle load with AVF flow only in lower arm, but not in upper arm AVFs. Our study results are in agreement with Basile et al (21), showing that higher AVF flow (more commonly seen in upper arm access) failed to associate with higher cardiac risk.…”
Section: Discussionsupporting
confidence: 93%
“…However, recent data suggest that the relationship between Qa and CO is not linear; a third‐order polynomial regression model best fits this relationship with a curve consisting of an initial plateau of CO followed by a steep slope with CO rising more sharply at greater Qa (Table ). Furthermore, Basile et al recently showed that the relationship between Qa and the workload of the LV also follows a third‐order polynomial regression model. The causes of this phenomenon are not known, but one can hypothesize a sort of myocardial functional reserve and, then, of myocardial adaptation, capable of sustaining increases of Qa in the long‐term without the precipitation of heart failure (HF).…”
Section: The Impact Of An Arteriovenous Access On Hemodynamic and Cirmentioning
confidence: 98%
“…Of note, the arteriovenous access and the systemic circulation are connected in a parallel way. Reproduced from Basile et al with permission from Oxford University Press. [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: The Impact Of An Arteriovenous Access On Hemodynamic and Cirmentioning
confidence: 99%
“…The causal link between access flow and increased morbi-mortality probably exists, but still needs to be directly proven [8, 50]. …”
Section: Haemodynamic Impacts Of High-flow Avf In Patients Under Chromentioning
confidence: 99%
“…AVF referral within ∼12 months of the estimated time to dialysis performed best among time frame strategies, although the timing of referral is classically guided by the patient’s age and by his/her individual likelihood and rate of progression to ESRD [6, 7]. The AVF flows in the forearm usually reach 500–900 mL/min, whereas those in the upper arm are 900–1500 mL/min [2, 8]. Inherently, AVF causes significant haemodynamic changes in patients under chronic HD, which may lead to serious complications, including arterial steal, pulmonary hypertension (PH) and high-output cardiac failure [9].…”
Section: Introductionmentioning
confidence: 99%